A Change in Ocular Circulation after Photocoagulation for Retinopathy of Prematurity in a Neonate - Matsumoto, Tadashi (Case Rep Ophthalmol, 2017)
BACKGROUND: The dilation of veins and tortuosity of arteries that occur in retinopathy of prematurity (ROP) are improved by therapy, and thus posttherapy changes in ocular circulation are also conceivable. We report a case of ROP in which we were able to measure the ocular circulation before and after photocoagulation therapy, using a laser speckle flowgraphy (LSFG) system that is modified for neonates. CASE REPORT: A female infant was born at 25 weeks' gestation with a birth weight of 808 g. We performed photocoagulation in both eyes at age 15 weeks, and we measured the ocular circulation with the “LSFG-baby” system before and at 12 weeks after the photocoagulation treatment. We also measured the mean blur rate (MBR) in the optic nerve head (ONH) and the relative flow volume (RFV) in the retinal vessels, and we examined the change rates from before to after treatment. The changing rate of the MBR-A (the mean of all values) in the ONH in the right and left eyes was 76.5 and 98.5%, respectively. The vascular RFV in the severe dilation and tortuosity quadrant also tended to decrease. CONCLUSIONS: Photocoagulation improved the dilation of veins and tortuosity of arteries and reduced the ocular blood flow in this neonate with ROP. The LSFG-baby system effectively and directly revealed the optic nerve and retinal blood vessels.